On Lateral-Torsional Buckling of Non-Local Beams (Advances in Applied Mathematics and Mechanics, 2018)
Nonlocal continuum mechanics allows one to account for the small length scale effectthat becomes significant when dealing with micro- or nano-structures. This paper dealswith the lateral-torsional buckling of elastic nonlocal small-scale beams. Eringen'smodel is chosen for the nonlocal constitutive bending-curvature relationship. The effectof prebuckling deformation is taken into consideration on the basis of the Kirchhoff-Clebschtheory. It is shown that the application of Eringen's model produces small-length scale termsin the nonlocal elastic lateral-torsional buckling moment of a hinged-hinged strip beam.Clearly, the non-local parameter has the effect of reducing the critical lateral-torsionalbuckling moment. This tendency is consistent with the one observed for the in-plane stabilityanalysis, for the lateral buckling of a hinged-hinged axially loaded column. The lateralbuckling solution can be derived from a physically motivated variational principle.